The Effect of Perceived Organizational Support on Turnover Intention Mediated by Job Satisfaction and Burnout - Kusuma, Eko Pria; Wiwoho, Gunarso; Helmy, Irfan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study was to determine the effect of perceived organizational support, job satisfaction, and burnout on turnover intention of nurses at Purwogondo Hospital. The sample population was 80 nurses working at Purwogondo Hospital. The questionnaire was distributed through direct questionnaire distribution to nurses. SPSS software version 22 was used to model the relationship between the variables studied. The results of the study confirmed a positive relationship between perceived organizational support and job satisfaction and a negative relationship with burnout. Job satisfaction had a negative effect on turnover intention, burnout had a negative effect on job satisfaction and a positive effect on turnover intention. The results showed a mediating effect of job satisfaction and burnout on the relationship between perceived organizational support and turnover intention. Based on the model presented in this study, it can be concluded that perceived organizational support has an impact on job satisfaction, burnout and turnover intention.